An integrated understanding of academics knowledge sharing behaviour: A comparative study on HLIs. Issue 1 (15th May 2020) - Rahman, Muhammad Sabbir; Abdel Fattah, Fadi Abdel Muniem; Hassan, Hasliza; Haque, Tayeenul
Abstract : Purpose: The purpose of this study is to examine the underlying functions of sense of spirituality (SS), emotional intelligence (EI) and perceived work environment (PWE) towards knowledge sharing behaviour (KSB) among the academic staff of higher learning institutions (HLIs) through a comparative investigation. This study extends the investigation by examining the relationship between SS and KSB through the mediating role of EI. The moderating role of PWE between SS and KSB was also tested. Design/methodology/approach: The sample comprised 300 responses from 150 Bangladeshi and 150 Malaysian academic staff of public and private HLIs. Convenient sampling tools were used. Structural equation modelling (SEM) was used to analyse the proposed model and hypotheses. The study explains the differences and similarities in KSB practices concerning SS, EI and PWE of the academic staff from the two countries' HLIs. Findings: The results support the direct positive effects of SS on KSB. The two data sets also support the indirect effects of SS on KSB through the mediation of EI. However, the results indicate that SS only promoted KSB among individuals with high levels of PWE in their respective institutions. For individuals with low levels of PWE, SS did not affect KSB. Practical implications: The management of HLIs should engage their experiences and those of newly hired academic staff in the KSB process. However, in facilitating KSB culture among the academic staff, HLIs need to foster the staff's SS, which ultimately improvises the EI to strongly influence KSB. The management of HLIs understands that SS may be inefficient in promoting KSB among employees with low PWE. Authorities of HLIs need to facilitate a quality work environment to enhance the association between SS and KSB. Originality/value: This study is one of the initial attempts to investigate KSB by considering SS, EI and PWE in the context of Bangladesh and Malaysia HLIs. The findings of the study can serve as inputs to HLIs in developing best practices across KSB dimensions and improving academic staff performance.